Recent Advances in 2D Rare Earth Materials. (27th December 2020) - Chen, Ping; Han, Wei; Zhao, Mei; Su, Jianwei; Li, Zexin; Li, Dongyan; Pi, Lejing; Zhou, Xing; Zhai, Tianyou
Abstract: 2D rare earth (RE) materials have received considerable attention in recent years due to the fascinating luminescence, magnetism, and electric properties originated from RE associated with sharp and various emission peaks, intrinsic 2D ferromagnetism, and incommensurate charge density wave. These materials might open up a new prospect in next‐generation lighting, magnetic devices, and phototransistors. Herein, a comprehensive review of 2D RE materials is presented, focusing on their recent progresses. First, the crystal structures of 2D RE materials are discussed. Then, typical synthesis methods such as mechanical exfoliation, molecular beam epitaxy, pulsed laser deposition, and chemical vapor deposition are introduced. Furthermore, various properties in luminescence, magnetism, and electronics are summarized. The recently reported RE‐based 2D novel photodetectors are outlined as three constructions: MoS2 /RE, graphene/RE, and perovskite/RE, which show promising applications for both narrow and broad band detection arised from the special absorption windows of different RE elements. Finally, the conclusions and outlook of this area are proposed, such as exploring novel 2D RE compounds, improving stability, and broadening applications. Abstract : This work reviews the recent advances in 2D rare earth materials, which are the rising star in 2D applications. The crystal structure, synthesis methods, properties, and applications of 2D rare earth materials are summarized. Finally, the problems, future challenges, and new opportunities of this area are also discussed.